2019
DOI: 10.1038/s41467-019-09091-3
|View full text |Cite
|
Sign up to set email alerts
|

Human olfactory-auditory integration requires phase synchrony between sensory cortices

Abstract: Multisensory integration is particularly important in the human olfactory system, which is highly dependent on non-olfactory cues, yet its underlying neural mechanisms are not well understood. In this study, we use intracranial electroencephalography techniques to record neural activity in auditory and olfactory cortices during an auditory-olfactory matching task. Spoken cues evoke phase locking between low frequency oscillations in auditory and olfactory cortices prior to odor arrival. This phase synchrony oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 71 publications
4
43
1
Order By: Relevance
“…In line with recent reports on phase synchrony required for olfactory-auditory integration (Zhou et al, 2019), each trial began with an audio-recorded label (2 s), followed by presentation of an odor A (6 s). Subsequently, participants heard a different label (2 s) before odor B (6 s), and then another label (2 s) before odor X (6 s).…”
Section: Methodsmentioning
confidence: 85%
“…In line with recent reports on phase synchrony required for olfactory-auditory integration (Zhou et al, 2019), each trial began with an audio-recorded label (2 s), followed by presentation of an odor A (6 s). Subsequently, participants heard a different label (2 s) before odor B (6 s), and then another label (2 s) before odor X (6 s).…”
Section: Methodsmentioning
confidence: 85%
“…We also did not observe a reset of the phase of beta oscillations by the sound in the olfactory structures. We cannot exclude that in our data, the way our stimuli are presented masks phase resetting, as it has recently been shown that phase synchrony occurs in an olfactory-auditory integration in human when the two modality did not arrive simultaneously 35 . However, using PCI analysis we detect sharper strips for the OS− condition compared to the S+ condition (Suppl.…”
Section: Discussionmentioning
confidence: 85%
“…A human fMRI study by Gottfried et al(2003) showed that visual facilitation of olfactory detection enhanced activity in the OFC which is distinct from, but interconnected with, the POC [66]. Using phase synchrony, Zhou et al (2019) showed that primary olfactory cortical areas support multisensory integration within the olfactory system [67]. Additionally, simultaneous presentation of pure trigeminal and pure olfactory stimuli led to higher cortical activation in the OFC and insula (INS), although this study did not demonstrate the integration of olfactory and trigeminal stimuli in the POC [68].…”
Section: Discussionmentioning
confidence: 99%